2005
DOI: 10.1080/01969720591008922
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Fuzzy Time Series on a Heuristic High-Order Model

Abstract: Chen first proposed the high-order fuzzy-time series model to overcome the drawback of existing fuzzy first-order forecasting models. His model involved easy calculations and forecasted more accurately than the other models. This study proposes an enhanced fuzzy-time series model, called heuristic high-order fuzzy time series model, to deal with forecasting problems. The proposed model aims to overcome the deficiency of Chen's model, which depends strongly on the highest-order fuzzy-time series to eliminate am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…Later, Own and Yu [11] extended Chen's model [9] as a heuristic high-order fuzzy time series model, which depends strongly on the trend of fuzzy time series. Huarng and Yu [12,13] applied neural networks and type 2 fuzzy set to refine the fuzzy relationships and further build up forecasting accuracy.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Later, Own and Yu [11] extended Chen's model [9] as a heuristic high-order fuzzy time series model, which depends strongly on the trend of fuzzy time series. Huarng and Yu [12,13] applied neural networks and type 2 fuzzy set to refine the fuzzy relationships and further build up forecasting accuracy.…”
Section: Introductionmentioning
confidence: 98%
“…In spite of the aforementioned approaches, the most commonly used method for interval partitioning, perhaps, is equalwidth partition [1,3,[5][6][7]9,11,16,23], however when the distribution of the continuous values is not uniform, it might not yield good results [24]. In addition, it has been recently shown that using unequal-sized intervals might produce better forecasting accuracy than traditional equal-width partitioning [22].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Chen [7] generalized their previous work [4] to deal with high-order time series, and high-order models have subsequently received more attention in the literature. Own and Yu [8] combined the concepts of fuzzy logic relationship groups and domainspecific heuristic knowledge, and proposed a forecasting model using a trend heuristic for fuzzy time series, while Lee et al [9] similarly extended Chen's model [7] to allow two-factor high-order time-invariant forecasting. Although high-order models have been shown to improve forecasting accuracy, there is a significant problem with regard to determining an appropriate order number and order redundancy.…”
Section: Introductionmentioning
confidence: 99%
“…In time-invariant fuzzy time series, several researchers have proposed various forecasting methods (Song and Chissom 1993b;Chen 1996;Huarng 2001a;Chen 2002;Lee and Chou 2004;Huarng and Yu 2005;Own and Yu 2005;Tsaur et al 2005;Yu 2005a,b;Chen and Chung 2006;Lee et al 2006;Liu 2007). Their forecasting methods often form fuzzy logical relationships (such as A i → A m , A i , .…”
mentioning
confidence: 99%